LAW OF RESTORATIVE JUSTICE IN THE PROCESS OF EXECUTION OF THE SENTENCE IN COSTA RICA, AND ITS APPLICATION IN VULNERABLE POPULATIONS: WOMEN SENTENCED TO THE SUBSTITUTE PENALTY OF HOUSE ARREST WITH ELECTRONIC MONITORING - Jiménez Rodríguez, Daniel (2025)
Restorative Justice is a paradigm that believes in restoring the harm done by the offender to the victim of a crime. Its practices are ancestral, but as a model of justice it is novel, although it has been shown that in the ordinary criminal process it has been successful, because it gives the victim a voice, and  motivates the offender to restore the injury inflicted; it contributes to the penal system in its desire to restore social coexistence altered by the commission of a crime.The penal system in Costa Rica allows the implementation of this model of justice in all phases of the process, including the execution of sentence. However, there are doubts about its usefulness for this procedural moment, and if in the way in which it is regulated in Costa Rican law turns out to be applicable at the stage of execution of sentence, especially when it is required by individuals in a state of vulnerability, such as women sentenced to an alternative sentence of house arrest with electronic monitoring.